Organizational mindfulness and continuity management in small and medium-sized enterprises - Aho, Atso (My University, 2022)
Widespread dependency on information technology and information systems and subsequent ubiquitous information technology risk is not new. Approaches to analyzing and mitigating information technology risks have been developed, but traditionally the frameworks have been more suitable for larger enterprises. A framework suitable for a small and medium-sized enterprise (SME) has been developed, but how it enables resilience and how applicable it is without consultants is yet to be studied. Organizational mindfulness’ cognitive processes have been explored, but their application to a SME context has been neglected. Research on SMEs preparing for continuity issues have focused on the risk perception and behavioral aspects of owner-managers. An action research study was conducted in a Finnish SMEs that provides retail digitalization services to provide and improve understanding of organizational mindfulness in an SME context. This study examines how an SME starts to formalize their continuity measures and utilizes a novel framework. The findings point to the applicability of organizational mindfulness’ cognitive processes to SMEs and describe how the mindfulness’ concepts are manifested in an SME. The findings also support the framework enabling the SME to understand and utilize the mindfulness processes.

Yleinen riippuvuus informaatioteknologiasta ja tietojärjestelmistä on tunnistettu ilmiö. Keinoja riskien huomioiseksi on olemassa, mutta ne soveltuvat perinteisesti suurille yrityksille. Pienille ja keskisuurille yrityksille (pk-yrityksille) soveltuva malli on kehitetty, mutta sen käytettävyyttä ilman konsultteja ei tunneta. Ei myöskään ole tutkittu kuinka pk-yritykset voivat mallin avulla lisätä resilienssiään. Organisaatioiden mindfulnessin kognitiivisia prosesseja on aiemmin tutkittu, mutta niiden soveltuvuutta pk-yrityksiin ei tunneta. Tutkimus pk-yritysten jatkuvuudenhallinnasta on keskittynyt kuvaamaan omistajayrittäjien käyttäytymistä ja riskien havainnointia. Toimintatutkimus suoritettiin suomalaisessa pk-yrityksessä, joka tarjoaa digitalisaation palveluita vähittäiskaupoille. Tutkimus kuvaa kuinka pk-yritys aloittaa tekemään jatkuvuudenhallintaa muodollisemmin ja hyödyntää siihen uutta jatkuvuudenhallinnan mallia. Löydökset viittaavat siihen, että organisaatioiden mindfulnessin kognitiiviset prosessit on sovellettavissa pk-yritysten kontekstissa. Ne viittaavat myös pkyrityksille kehitetyn jatkuvuudenhallinnan mallin tukevan yritystä näiden prosessien tunnistamisessa ja hyödyntämisessä.
Keywords: business continuity management (BCM), small and medium-sized enterprise (SME), resilience, organizational mindfulness